2012
DOI: 10.1371/journal.pntd.0001958
|View full text |Cite
|
Sign up to set email alerts
|

Cruzipain Promotes Trypanosoma cruzi Adhesion to Rhodnius prolixus Midgut

Abstract: Background Trypanosoma cruzi is the etiological agent of Chagas' disease. Cysteine peptidases are relevant to several aspects of the T. cruzi life cycle and are implicated in parasite-mammalian host relationships. However, little is known about the factors that contribute to the parasite-insect host interaction.Methodology/Principal FindingsHere, we have investigated whether cruzipain could be involved in the interaction of T. cruzi with the invertebrate host. We analyzed the effect of treatment of T. cruzi ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…The expression of surface gp63-like molecules in the insect trypanosomatid Herpetomonas samuelpessoai was drastically enhanced after passage in the insect host model Aedes aegypti gut (Branquinha et al 2013). In addition, T. cruzi cells isolated after passage in the insect vector R. prolixus presented a drastic increase in the expression of surface cruzipain (Uehara et al 2012). Although the interaction step was not performed in vivo, our results revealed that a significant increase in the surface gp63-like and cruzipain-like expression was detected, which is very suggestive of their involvement in the interaction process of the parasite with the invertebrate vector.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of surface gp63-like molecules in the insect trypanosomatid Herpetomonas samuelpessoai was drastically enhanced after passage in the insect host model Aedes aegypti gut (Branquinha et al 2013). In addition, T. cruzi cells isolated after passage in the insect vector R. prolixus presented a drastic increase in the expression of surface cruzipain (Uehara et al 2012). Although the interaction step was not performed in vivo, our results revealed that a significant increase in the surface gp63-like and cruzipain-like expression was detected, which is very suggestive of their involvement in the interaction process of the parasite with the invertebrate vector.…”
Section: Resultsmentioning
confidence: 99%
“…In the interpretation, since no T. cruzi DNA quantitation was performed, it is interpreted as positive DNA amplification in Cts < 38 and negative amplification as absence. 12S subunit ribosomal gene of triatomines was used as internal amplification control under the conditions and primers previously described [19]. Subsequently, the insects with positive results by qPCR were submitted to kinetoplast DNA amplification using primers 121 (5′-AAA TAA TGT ACG GGK GAG ATG CAT GA-3′) and 122 (5′-GGT TCG ATT GGG GTT GGT GTA ATA TA-3′) to discriminate T. cruzi and T. rangeli infections as previously reported [20].…”
Section: Methodsmentioning
confidence: 99%
“…After the blood meal and trypomastigote-into-epimastigote differentiation, T. cruzi epimastigotes migrate to the gut of the insect vector, where they divide and adhere strongly to perimicrovillar membranes in the posterior midgut [52] . The adhesion process of epimastigotes to these membranes is modulated by the participation of glycoconjugates exposed on the surface of the parasite, as glycoinositol phospholipids (GIPLs) and cruzipain [53] , [54] , but several proteins found in perimicrovillar membranes appear to be involved in this process as well [52] . However, the participation of other parasite surface molecules, such as gp72 [55] , mucins [56] and Tcgp63 [57] cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%